2022
DOI: 10.1177/11786302221114738
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic Child Feces Disposal Practice and Its Associated Factors among Mothers/Caregivers of Under Five Children in West Armachiho District, Northwest Ethiopia

Abstract: Background: Children’s feces are 5 times more dangerous than that of adults. Unhygienic disposal of child feces has been reported as one of the major sanitation problems in Sub-Saharan African countries. However, there is a scanty of information in the study area and evidences are insufficient in Ethiopia. Therefore, this study intends to assess child feces disposal practices and associated factors among Mothers/Caregivers of Under Five Children in West Armachiho District, Northwest Ethiopia. Methods: A commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Before being included in the review, each original study's quality was assessed using the Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument (JBI). Our analysis revealed that, out of the 15 included studies, 86.7% had a low risk of bias [15,23,24,[26][27][28][29][30][31][32][33][34][35][36] and the remaining 13.3% had a moderate risk of bias [25,37] (S2 Table ).…”
Section: Included Study Qualitymentioning
confidence: 93%
See 1 more Smart Citation
“…Before being included in the review, each original study's quality was assessed using the Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument (JBI). Our analysis revealed that, out of the 15 included studies, 86.7% had a low risk of bias [15,23,24,[26][27][28][29][30][31][32][33][34][35][36] and the remaining 13.3% had a moderate risk of bias [25,37] (S2 Table ).…”
Section: Included Study Qualitymentioning
confidence: 93%
“…In a total of 616 published studies were retrieved and from these 15 cross-sectional studies that met inclusion criteria and reported about the influence of improved latrine facility ownership on household child excreta disposal behaviors were included in this study [15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. In process due to overlap about 166 studies were removed from the records.…”
Section: Study Selection Proceduresmentioning
confidence: 99%
“…26 Hygienic or safe disposal of children's stools is influenced by individual and contextual variables and has been demonstrated in a handful of studies. [27][28][29][30] In most of these studies, the practices of safe disposal of children's stools were low. In a recent survey of 15 SSA countries, it was found that only 58.73% of childbearing women safely disposed of their children's stools which varied from 26.38% in Chad to 85.90% in Rwanda.…”
Section: Introductionmentioning
confidence: 99%